2018
DOI: 10.1002/sia.6519
|View full text |Cite
|
Sign up to set email alerts
|

ZnO superhydrophobic coating via convenient spraying and its biofouling resistance

Abstract: The attachment of microbial biomass on solid surfaces, also referred to as biofouling, is a universal phenomenon that occurs in natural and engineering systems. However, traditional antibiofouling surfaces based on either the release of biocidal compounds or surface chemical/physical design have some drawbacks, such as the high cost, the complicated process, the low accuracy, and the limitation to achieve coatings over large area. Herein, to overcome these problems, a superhydrophobic coating is fabricated via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The surface wettability of the surface was found to be influenced by the size of zinc oxide nanoparticles, in which 100 nm nanoparticles demonstrated a water contact angle and sliding angle of 150.5° and 24.5°, respectively, whereas 10 nm nanoparticles presented with a much rougher surface and higher superhydrophobicity, indicated by a water contact angle and sliding angle of 169.3° and 2.5°, respectively. The study also showed that durability can be increased by using a mixture of 10 nm and 100 nm nanoparticles, where the superhydrophobicity of such a coating is comparable to those of 10 nm nanoparticles, with a water contact angle and sliding angle of 168.5° and 3.5°, respectively [ 106 ].…”
Section: Nanomaterials For Fabrication Of Superhydrophobic Surfacesmentioning
confidence: 99%
“…The surface wettability of the surface was found to be influenced by the size of zinc oxide nanoparticles, in which 100 nm nanoparticles demonstrated a water contact angle and sliding angle of 150.5° and 24.5°, respectively, whereas 10 nm nanoparticles presented with a much rougher surface and higher superhydrophobicity, indicated by a water contact angle and sliding angle of 169.3° and 2.5°, respectively. The study also showed that durability can be increased by using a mixture of 10 nm and 100 nm nanoparticles, where the superhydrophobicity of such a coating is comparable to those of 10 nm nanoparticles, with a water contact angle and sliding angle of 168.5° and 3.5°, respectively [ 106 ].…”
Section: Nanomaterials For Fabrication Of Superhydrophobic Surfacesmentioning
confidence: 99%
“…In the case of non-biocide release coatings, they can be divided into different categories: (a) coatings that detach biofoulants (i.e., hydrophobic materials, such as fluorocarbons, hydrocarbons, and polydimethylsiloxanes); (b) coatings that inhibit microbial growth [ 49 , 96 ]; (c) coatings that prevent attachment of biofoulants (such as PEG-based materials for their resistance to protein adsorption and cells adhesion, or antimicrobial peptides) [ 1 , 97 , 98 , 99 ]; or (d) materials able to create a superhydrophobic surface, based on ZnO NPs functionalized with hexadecyltrimethoxysilane [ 100 ], or pluronic-lysozyme conjugate coatings [ 101 ]. Thus, the measurement of microbial adhesive forces represents a crucial topic [ 102 ].…”
Section: Enhancement Of Antimicrobial Properties Via Nanomodification Of Epoxiesmentioning
confidence: 99%
“…Owing to their unique properties, superhydrophobic coatings can be used in self-cleaning [ 1 , 2 , 3 , 4 , 5 ], anti-corrosion [ 6 , 7 , 8 ], anti-icing [ 8 , 9 , 10 ], and oil–water separation [ 10 , 11 , 12 ], suggesting great potential in a broad range of applications [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. ZnO nanoparticle (nano-ZnO) has strong anti-bacterial properties because of its low volume and high surface activity [ 23 , 24 , 25 ]. Hsieh et al [ 26 ] successfully prepared a superhydrophobic coating using a composite of ZnO and fluorinated polymer.…”
Section: Introductionmentioning
confidence: 99%